Patient Complaint Cases in Primary Health Care: What Are the Characteristics of General Practitioners Involved? - Birkeland, Søren (Hindawi Publishing Corporation, 2013)
Background. Limited knowledge exists about factors increasing the risk of general practitioners becoming involved in a complaint case or getting disciplined in connection with a complaint case. Aim. The present study aimed to identify the general practitioner and practice characteristics associated with complaint cases and discipline. Methods. Information on general practitioners involved in complaint case decisions during one year (2007) was linked to Danish National register data on all general practitioners (n = 3,765). Logistic regression was used for statistical analysis. Results. With regard to complaints concerning daytime services (n = 265), the professional seniority of the general practitioner was positively associated with the odds of receiving a complaint decision (OR = 1.44 per 20 years of seniority; CI 95%, 1.04–1.98). Likewise, having more consultations per day was associated with increased odds (OR = 1.29 per 10 extra consultations per day; CI 95%, 1.07–1.54). No statistically significant association could be demonstrated between being disciplined and general practitioner or practice characteristics. Conclusion. The possible relationship between professional seniority, rate of consultations, and complaint cases merits further studies to clarify the impact of professional seniority and workload on professional performance and to furthermore consider the role of factors such as job content and communication styles.